Toward a Unified Theory of the CSP–CFP Link - Marom, Isaiah Yeshayahu (Journal of business ethics, 2006)
This article proposes a unified theory of the relationship between corporate social performance (CSP) and corporate financial performance (CFP). The theory provides a framework for rationalizing the various and contradictory findings in past empirical research. The theory is based on the parallels between the business and CSR domains, and thus draws on models from economics.